The Apache : nomadic hunters of the Southwest - Englar, Mary (Mankato, Minn. : Bridgestone Books, 2003)
Looks at the customs, family life, history, government, culture, and daily life of the Apache people of Oklahoma, New Mexico, and Arizona.
Who are the Apache? -- Traditional life -- Spanish and Americans bring change -- The Apache today -- Sharing the traditions.
Keywords: Apache Indians -- Juvenile literature; Indians of North America